Kemampuan Penalaran Matematis dalam Menyelesaikan Soal Geometri ditinjau dari Persepsi Siswa - Fauziyah, Fida Dinar; Sujarwo, Imam (Galois: Jurnal Penelitian Pendidikan Matematika, 2022)
Mathematical reasoning ability is a person's ability to think logically in drawing a conclusion from problem solving in the mathematics learning process. By thinking logically, students can have confidence that the mathematics they learn is reasonable so that it affects the mathematical information and knowledge that students receive. It will also lead to different perceptions of each student in participating in mathematics learning. To determine the ability of mathematical reasoning when viewed from the perception of students, it can be done by giving geometry questions. The purpose of this study was to describe the mathematical reasoning ability of students with positive and negative perceptions in working on geometry problems. This research uses a qualitative approach with exploratory descriptive research. This research was conducted at SMPN 2 Balongbendo with the research subjects of two students of class VIII E, with each of them being a student with positive perceptions and a student with negative perceptions. Data collection techniques used are tests and interviews, while to determine the validity of the data using time triangulation. The results of this study indicate that students with positive perceptions can achieve every indicator of mathematical reasoning ability. While students with negative perceptions have not been able to fulfill every indicator of mathematical reasoning ability.